Inside Front Cover. Issue 2 (23rd June 2020) - Unknown
Abstract : Abstract : Inside Front Cover This paper presents a rare example of aggregation‐induced emission luminogens (AIEgens) as a highly efficient photo‐catalyst for pollutant decomposition in an environmentally relevant application. The presence of AIE would induce OH for further photocatalytic degradation processes under sunlight irradiation and purifying the water environment. This research opens up new avenues for the application of AIE research.